Pengaruh Work Life Balance, Job Burnout, Dan Workload Terhadap Organitational Commitment Pada Perawat Wanita RSI Unisma Malang - Eki Alifatul Ariyanti; Pardiman Pardiman; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis study was conducted to determine and analyze the effect work life balance, job burnout and workload on organizational commitment female nurses. The type of research used is a quantitative approach. The population in this study at the Islamic Hospital Unisma Malang with 65 people with a saturated sample of as much as the total population. Data collection techniques using a questionnaire with a likert scale. The data analysis technique in this study uses classic assumption test, multiple regression, t-test, F-test and coefficient of determination which is processed using the SPSS software progam (version 14.0). The results of this study indicate that simultaneously work life balance, job burnout and workload have a positive and significant effect on organitational commitment. Partially, work life balance has a significant positive effect on organitational commitment, job burnout variable has no effect on organitational commitment, and workload has a significant negatif effect on organitational commitment. Keywords: work life balance, job burnout and, workload, and organitatonal commitment